Tecnología de captura y almacenamiento de CO2 en sectores industriales (2017)
This monograph analyzes carbon capture and storage technology (CAC) as an artificial sink and its contribution to mitigate the effects of global warming. With a systematic review of information, the carbon dioxide (GEI) and its effects on global warming, the role and characteristics of natural and artificial sinks are studied; also the industrial sectors, specifically the construction sector, focused on the cement industry and the energy sector, as they are important (GEI) generators.